HOW TO INCREASE EMPLOYEE’S DISCIPLINARY IN FACULTY MEDICINE OF DIPONEGORO UNIVERSITY - Setyowati, Retno (JURNAL BISNIS STRATEGI, 2011)
Human Capital plays an important role in organization. It is the heart of the organization strategy. Many factors embeded in it. Public Service employees as government human capital instead of the contract employees. The quality of the Public Service Employee has recently become a major issue. It is widely known that Public Service employee is lacking of disciplin. The issue discuss most in Public service employee’s disciplinary is absentheeism. This study presents factors that influence the Public Service employee’s disciplinary in Faculty of Medicine of Diponegoro University.This research purposes will support the decision – making process to increase the Faculty of Medicine of Diponegoro University employee’s disciplinary, this study proposing some models analyzed by SEM. The study population is administration staffs in Faculty of Medicine of Diponegoro University for both Public Service employees and contract employees. The respondents are 120 employees whose given some questionaires related to the study.The result of the data analysis shows that the human capital is influenced by knowledge sharing, empowerment and workplace environment. Whilst human capital influences employee’s disciplinary positively.